Building Blocks of Knowledge Management Enablers in the Hotel Sector in Kenya - Korir, Jacqueline Cheptepkeny (African Journal of Education,Science and Technology (AJEST), 2018)
This paper addresses the need to conceptualize knowledge management enablers for easy use in hospitality management in order to improve the information basis for decision making. It examines indicators used to measure knowledge management enablers and enhances understanding of the factors. The paper contributes to empirical knowledge pertaining to knowledge management particularly in the hospitality industry. Previous studies measured knowledge management enablers using social-technical theory and social-technical perspectives. The study employed both descriptive and explanatory research designs. The target population for the study was 756 employees from three selected hotels out of which 254 formed the sample size. Purposive, proportionate, stratified and systematic random sampling methods were used for the study to realize the objective of the study. Self administered questionnaire were used to collect data. Validity and reliability tests were undertaken. Cronbach’s alpha was at the level of 0.934. Data was analysed using descriptive and factor analysis to test the strength of the indicators of knowledge management enablers. Findings from this study revealed that knowledge management enablers in the hotel setting can be measured using personal knowledge and social knowledge.